Cold scissors ploughing technique in hysteroscopic adhesiolysis: a comparative study - Zhao, Xingping (Ann Transl Med, 2020)
BACKGROUND: Intrauterine adhesions (IUAs) can be dissected using hysteroscopic scissors (cold scissors) or other methods, but there is no consensus on which hysteroscopic method is preferable. There is also no consensus on the method of how to deal with the scar tissue on the surface of the intrauterine cavity. METHODS: From January 2016 to October 2017, 179 patients who had HA met the enrollment criteria (see the text below), and their data were analyzed retrospectively. In addition, all patients were divided into three groups according to the surgical techniques used. The groups were the ploughing group (PG) (using cold scissors to dissect the adhesion and cut the scar tissue using a ploughing technique) (n=81), the traditional group (TG) (using cold scissors to dissect the adhesion, but not deal with the scar tissue) (n=42), and the electrosurgical group (EG) (using a resectoscope to dissect the adhesion with an energy L-hook electrode, and not deal with the scar tissue) (n=56). Safety (surgical complications), feasibility (surgical technique replacement rate), and postoperative efficacy (reduction of AFS score, pregnancy, and live birth rate), were each evaluated between groups. RESULTS: No statistically significant differences between the groups were observed in basic preoperative information (P>0.05), while there were significant differences between PG and TG, as well as PG and EG in postoperative AFS scores (PG vs. TG: P=0.007; PG vs. EG: P<0.001) and pregnancy outcome (PG vs. TG: P=0.039; PG vs. EG: P<0.001). No patients had surgical complications such as uterine perforations, moderate or severe fluid overload, heavy uterine bleeding, nor any surgical technique replacements (for example, transfer to use a resectoscope). CONCLUSIONS: Cold scissors ploughing technique in HA is effective, feasible, and safe, and thus worthy of further study.